2002
DOI: 10.2308/accr.2002.77.1.203
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence on the Extent and Origins of JIT's Profitability Effects

Abstract: Empirical research provides scant evidence that just-in-time (JIT) adopters outperform their non-adopting industry peers. Using a sample of 201 JIT adopters and matched non-adopters, we examine the relation between financial performance and JIT. Our sample-wide results indicate that JIT adopters improve financial performance relative to non-adopters, and that profit margin, rather than asset turnover, is the primary source of such improvement. However, results of additional analyses suggest that JIT adopters b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(155 citation statements)
references
References 4 publications
8
144
0
3
Order By: Relevance
“…These three measures were obtained from Compustat. Although interdependent, ROA and ROS reflect different determinants of a business success or failure (Kinney and Wempe, 2002). For example, Atkinson et al (2001) describe asset turnover as a measure of productivity -the ability to generate sales with a given level of investment -and ROS as a measure of efficiency -the ability to control costs at a given level of sales activity.…”
Section: Firm Profitabilitymentioning
confidence: 99%
“…These three measures were obtained from Compustat. Although interdependent, ROA and ROS reflect different determinants of a business success or failure (Kinney and Wempe, 2002). For example, Atkinson et al (2001) describe asset turnover as a measure of productivity -the ability to generate sales with a given level of investment -and ROS as a measure of efficiency -the ability to control costs at a given level of sales activity.…”
Section: Firm Profitabilitymentioning
confidence: 99%
“…27 Previous research has suggested that business size is likely to interact with marketing and operational practices, leading to a different effect on firm performance (Kinney & Wempe, 2002). In this regard, we consider sales turnover as an objective measure of "business size".…”
Section: Comparing Performance Of Qandm Implementation Configurationsmentioning
confidence: 99%
“…Although interdependent, ROA and ROS reflect different determinants of a business success or failure (Kinney and Wempe, 2002). Atkinson et al (2001) describe asset turnover as a measure of productivitythe ability to generate sales with a given level of investment-and ROS as a measure of efficiency-the ability to control costs at a given level of sales activity.…”
Section: Survey Questionnaire and Variable Measurementmentioning
confidence: 99%